THE CASE METHOD. - Jackson, J. Hugh (The Accounting Review, 1926)
Abstract The article presents information on Harvard School method of case studies as experienced by the author himself. The Business School had operated for a number of years what was known as a Bureau for Business Research. That seemed to be the logical agency to begin the gathering of materials of this kind, and so the Bureau of Business Research was asked to obtain teaching materials for the development of the case method. In the beginning the Bureau of Business Research took a position which many of the professors in the school felt was quite unsound, namely, that any man whom they had on their staff could go out and gather cases in any field of business. It was the place where only people who can successfully gather cases are those with practical experience in that field of work; and at the present time the reorganization of the plans has not been completed the procedure which is being adopted as rapidly as possible is to have all of the cases gathered by men who have bad anywhere from ten to twenty years actual business experience. In other words, we are going to the other extreme for the time being. Men who are not even college men but men who have made a success in professional life, are being asked to come In and spend their time in helping bring together a body of materials which will be satisfactory for use as cases in the teaching of the various courses in the School.